Interaction between proatherosclerotic factors and right-to-left shunt on the risk of cryptogenic stroke: the Italian Project on Stroke in Young Adults. Issue 6 (23rd January 2012) - Pezzini, Alessandro; Grassi, Mario; Lodigiani, Corrado; Patella, Rosalba; Gandolfo, Carlo; Zini, Andrea; Musolino, Rossella; Calabrò, Rocco Salvatore; Bovi, Paolo; Adami, Alessandro; DeLodovici, Maria Luisa; Del Zotto, Elisabetta; et al.
Abstract : Objective: To explore the interaction effects between cardiac interatrial right-to-left shunt (RLS) and proatherosclerotic factors on the risk of brain ischaemia. Design: Multicentre Italian case–control study. Setting: University hospitals. Participants: 588 patients with cryptogenic stroke (CS) aged ≤45 years and 585 control subjects consecutively enrolled as part of the Italian Project on Stroke in Young Adults. Methods: Interaction effects between RLS and an individual proatherosclerotic score computed from the number of conventional vascular risk factors for the risk of CS were investigated. Data were examined by logistic regression models and expressed as interaction OR or interaction risk difference (RD). Results: CS risk increased with increasing number of proatherosclerotic factors in subjects without RLS (OR 2.73; 95% CI 1.98 to 3.76; RD +0.246; 95% CI +0.17 to +0.32; for subjects with one or more factors), but was higher in subjects with RLS and no additional proatherosclerotic factors (OR 5.14; 95% CI 3.49 to 7.58; RD +0.388; 95% CI +0.31 to +0.47) compared with subjects without RLS and no risk factors. Negative interaction and antagonistic effects between RLS and proatherosclerotic factors were observed (interaction OR 0.52; 95% CI 0.31 to 0.91; interaction RD −0.17; 95% CI −0.29 to −0.05). Conclusions: The influence of RLS on the risk of CS decreases with increasing number of atherosclerotic factors, and is highest when such factors are absent. Individual proatherosclerotic profiles may help to identify patients with CS whose patent foramen ovale is probably pathogenic.